Ekfrazno pesništvo pri Romanu Melodu in Pavlu Silentiariju - Širca, Alen Albin (Ars et humanitas, 2017)
The article about ekphrasis in Romanos the Melodist is based on the concept of ekphrasis in the context of Byzantine rhetoric and literature. In accordance with such a conception, which is basically the same as in ancient Greek rhetorical theory and practice, as explained in rhetorical textbooks, called progymnasmata, the simplest definition of ekphrasis is a speech that makes the subject matter vivid to the audience. As such, the current definition of ekphrasis, as the poetic description of a pictorial, sculptural or architectural work of art, is decidedly modern. After the introductory clarifications of the terminology, this article addresses the ekphrasis of Romanos the Melodist, the famous sixth-century Byzantine hymnographer who is the author of numerous kontakion. These can be considered as a kind of liturgical hymn, known for a number of poetic strategies, and are recognised as the pinnacle of Byzantine poetry. Romanos% use of ekphrasis in a biblical context is somewhat restrained. However, with the example of the naturalistic description of the Massacre of the Innocents, one that goes beyond the account in the Gospel of Matthew, and especially the thematization of rebuilding the Hagia Sophia, which is termed the Throne of God, Romanos sets the tone for Byzantine ekphrasis. A further architectural ekphrasis comes from another sixth century Byzantine poet, Paul the Silentiary. His most well-known work is the Descriptio ecclesiae Sanctae Sophiae. In particular in his description of the cupola of what was once the biggest church in Christendom, the Hagia Sophia, which is based on the interplay between light and darkness, we recognize that the phenomenon of light serves as an epiphanic experience: the Hagia Sophia thus becomes the material manifestation of divine revelation. Therefore, in Romanos, as in Paul, ekphrasis becomes a rhetorical device for expressing the unspeakable.
Keywords: bizantinska književnost; ekfraza; Hagia Sofia; literarne študije; Pavel Silentiarij; Roman Melod